B(C6F5)3‐Catalyzed Deoxygenative Reduction of Amides to Amines with Ammonia Borane. Issue 10 (23rd January 2019) - Pan, Yixiao; Luo, Zhenli; Han, Jiahong; Xu, Xin; Chen, Changjun; Zhao, Haoqiang; Xu, Lijin; Fan, Qinghua; Xiao, Jianliang
Abstract: The first B(C6 F5 )3 ‐catalyzed deoxygenative reduction of amides into the corresponding amines with readily accessible and stable ammonia borane (AB) as a reducing agent under mild reaction conditions is reported. This metal‐free protocol provides facile access to a wide range of structurally diverse amine products in good to excellent yields, and various functional groups including those that are reduction‐sensitive were well tolerated. This new method is also applicable to chiral amide substrates without erosion of the enantiomeric purity. The role of BF3  ⋅ OEt2 co‐catalyst in this reaction is to activate the amide carbonyl group via the in situ formation of an amide‐boron adduct. Abstract :